Social Cognitive Theory : A Bandura Thought Review published in 1982-2012 - Sri Muliati Abdullah (PSIKODIMENSIA, 2019)
This article was about reviewing ten of Albert Bandura's scientific works on Social Cognitive Theory published in journals, textbooks, and handbooks. Bandura has elaborated the social learning process with cognitive and behavioral factors that influence a person in the social learning process. The main identity of social cognitive theory was the introduction of the concept of human agency and the concept of triadic reciprocal determinism. Human agency has the meaning that human beings have the capacity to direct themselves through control over the thinking process, motivation and self-action. In the triadic model reciprocal determinism was discussed about the causes of reciprocal consequences of behavior, cognition and other personal factors, and environmental influences, in interacting interactions with one another. In addition to the above concept, Bandura also put forward on self efficacy. Self-efficacy perception occupies an important role in the causal structure of cognitive social theory because efficacy beliefs affect human ability to adapt to change, individually or collectively.